Do your own research! - Levy, NL (Springer, 2022)
Philosophical tradition and conspiracy theorists converge in suggesting that ordinary people ought to do their own research, rather than accept the word of others. In this paper, I argue that it’s no accident that conspiracy theorists value lay research on expert topics: such research is likely to undermine knowledge, via its effects on truth and justification. Accepting expert testimony is a far more reliable route to truth. Nevertheless, lay research has a range of benefits; in particular, it is likely to lead to greater understanding, even when it does not lead to knowledge. I argue that we can reap most of the genuine benefits of lay research while minimizing the risks by engaging in exploratory, rather than truth-directed, inquiry. To engage in exploratory inquiry is to engage dogmatically, expecting to be unable to confirm the expert view or to disconfirm rivals.